13-year-old-male with a left open humerus fracture with concomitant intramuscular mid-substance biceps rupture: A case report - Neil Pathak; Xuan Luo; Matthew D. Riedel (Trauma Case Reports)
A 13-year-old male presented with an open left humeral shaft fracture with intramuscular distal biceps rupture after being struck by a car. He underwent washout, humerus fixation, and open biceps repair. Immediate postoperative course was complicated by deep infection and failure of biceps repair. He subsequently required two additional surgeries. One year later, he exhibited full, painless elbow range of motion and biceps strength. This case is the first to report an open humeral shaft fracture with concomitant intramuscular, mid-substance biceps rupture in a pediatric patient. This was successfully treated with a full functional recovery.